Brightening dark excitons and trions in systems with a Mexican-hat energy dispersion: example of InSe - Lewis J. Burke; Mark T. Greenaway; Joseph J. Betouras (npj 2D Materials and Applications)
Abstract We investigate the properties of momentum-dark excitons and trions formed in two-dimensional (2D) materials that exhibit an inverted Mexican hat-shaped-dispersion relation, taking as an example monolayer InSe. We employ variational techniques to obtain the momentum-dark ground state and bright state (non-zero and zero quasiparticle momenta, respectively). These states are particularly relevant due to their peaks in the quasiparticle density of states, where for the momentum-dark ground state, the contribution here is largest due to the presence of a van Hove singularity (VHS). The momentum-dark systems require a brightening procedure to provide the necessary momentum to become bright. We study the brightening through coupling to phonons and compute the photoluminescence spectrum. This work opens new avenues of research, such as exploiting dark excitons in solar cells and other semiconductor-based optoelectronic devices.